Preparation method of three-layer co-extrusion mute composite pipe
By immersing the silica aerogel in a saturated ammonium carbonate solution and crystallization treatment, the weight and gravity coefficient are increased, the problem of difficult mixing between silica and resin is solved, and the uniform dispersion of silica aerogel in the middle layer resin is achieved, which significantly improves the silent effect and overall quality of the silent pipe.
Patent Information
- Application Number
- CN202411933428.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
When using silica aerogel in the prior art to prepare three-layer coextruded silent pipes, it is difficult to mix them evenly with silica and resin, resulting in uneven distribution of the sound-absorbing material in the middle layer and significantly reducing the quality of the pipe.
The silica aerogel is immersed in a saturated ammonium carbonate solution, and the ammonium carbonate solution is adsorbed into the pores of the silica aerogel, and the ammonium carbonate is crystallized in the pores of the silica aerogel by drying, increasing the weight and gravity coefficient of the silica aerogel, thereby achieving sufficient mixing in the middle layer resin. The middle layer blending is divided into one-stage kneading and two-stage kneading to ensure uniform dispersion of the silica aerogel.
Through the above method, the uniform dispersion of silica aerogel in the middle layer resin significantly improves the silent effect and overall quality of the silent pipe.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silent pipes, and in particular to a method for preparing a three-layer co-extruded silent composite pipe. Background Art
[0002] When using a drainage pipe, the water flow in the drainage pipe has irregular water hammer motion, which causes the pipe to generate a large noise, reducing the user's comfort. Therefore, in order to solve the above noise problem, the prior art proposes to set a guide in the pipe to guide the water flow inside the pipe, thereby reducing the pipe noise. For example, a spiral silent PVC-U pipe disclosed in publication number CN217559224 U regulates the fluid movement direction by setting spiral ribs inside the pipe, reduces the irregular water hammer motion, and achieves the purpose of reducing pipe noise.
[0003] In addition, CN 113085280 A in the prior art points out that the pipe can be formed into a three-layer structure, with the inner and outer layers made of high-strength, acid- and alkali-resistant materials and the middle layer made of sound-absorbing materials, so that the silencer pipe has multiple properties of silencer, high strength and corrosion resistance.
[0004] Prior art The silica aerogel disclosed in CN 109874089 B is a new sound-absorbing material published this year. Since it has a large number of holes inside, it can be used as a good sound-absorbing and noise-reducing material. Therefore, the present invention envisions combining silica aerogel, a three-layer co-extrusion structure and a spiral guide to prepare a silent pipe, but in actual operation, it is found that the silica aerogel particles are small and light in weight, and it is extremely difficult to mix it with the resin. The uneven distribution of the sound-absorbing material in the middle layer after the three-layer co-extrusion causes a significant reduction in the quality of the pipe. Summary of the invention
[0005] The present invention aims at the problem that silica and resin are difficult to be mixed evenly when using silica aerogel to prepare three-layer co-extruded silent pipes in the prior art, and provides a preparation method for a three-layer co-extruded silent composite pipe. The method immerses the silica aerogel in a saturated ammonium carbonate solution, so that the ammonium carbonate solution is adsorbed into the pores of the silica aerogel, and then the ammonium carbonate is crystallized in the pores of the silica aerogel by drying, and the silica aerogel is filled to significantly increase the weight of the silica aerogel, so that the silica aerogel can be fully mixed in the middle layer resin. In addition, the middle layer blending is divided into a first mixing stage and a second mixing stage. During the first mixing stage, the ammonium carbonate salt will not decompose to ensure that the silica aerogel can be evenly mixed in the middle layer resin. The second mixing stage increases the mixing temperature to decompose the ammonium carbonate salt in the silica aerogel into carbon dioxide, ammonia and water for discharge, thereby achieving uniform dispersion of the silica aerogel in the middle layer resin.
[0006] The specific technical scheme of the present invention is: A preparation method of a three-layer co-extruded silent composite pipe comprises the following steps: impregnating a silica aerogel in a saturated ammonium carbonate solution, drying and crystallizing the silica aerogel after the impregnation to obtain a precursor, blending the precursor with a middle-layer resin to obtain a middle-layer melt, blending an inner-layer resin to obtain an inner-layer melt, blending an outer-layer resin to obtain an outer-layer melt, and extruding the inner-layer melt, the middle-layer melt and the outer-layer melt to obtain the three-layer co-extruded silent composite pipe, wherein the middle-layer blending comprises a first-stage mixing and a second-stage mixing; the first-stage mixing is performed at a temperature of 140 to 150° C. and the time is 1 to 3 hours; the second-stage mixing is performed at a temperature of 180 to 190° C. and the time is 1 to 3 hours.
[0007] The present invention provides a method for preparing a three-layer co-extruded silent composite pipe, which solves the problem that silica aerogel is difficult to mix evenly in the middle layer resin. The present invention finds that the silica aerogel particles are small and light in weight. When the silica aerogel particles are directly mixed with the middle layer resin, the silica aerogel is minimally affected by the gravity coefficient, which makes it extremely difficult to disperse evenly in the melt. Therefore, in order to solve this problem, the present invention immerses silica in a saturated ammonium carbonate solution so that the ammonium carbonate solution enters the interior of the silica aerogel, and then crystallizes the ammonium carbonate solution in the silica aerogel through drying, so that the pore structure of the silica aerogel is filled with salt crystals, thereby significantly increasing the weight of the silica aerogel, thereby significantly increasing the gravity coefficient of the silica aerogel, and enabling the silica aerogel to be evenly dispersed in the middle layer resin.
[0008] The ammonium carbonate selected in the present invention can be decomposed into ammonia, carbon dioxide and water under heating conditions, so it can be completely removed from the pore structure of the silica aerogel after treatment, and will not affect the performance of the silica aerogel. The middle layer mixing of the present invention also adopts a two-stage mixing treatment method. The first stage mixing adopts a mixing treatment under the condition of lower than the decomposition temperature of ammonium carbonate and higher than the melting temperature of the middle layer resin. This step ensures that the precursor made of silica gel can be evenly dispersed in the middle layer resin. The second stage mixing adopts a temperature higher than the decomposition temperature of ammonium carbonate, so that the ammonium carbonate in the pores of the silica aerogel is decomposed into ammonia, carbon dioxide and water vapor. In the process of continuous stirring, all the generated gases are removed, thereby completing the uniform dispersion of the silica aerogel in the middle layer resin.
[0009] Preferably, the particle size of the silica aerogel is 100 to 500 μm.
[0010] Preferably, the middle layer resin is LDPE.
[0011] Preferably, the density of the LDPE is 0.90-0.93 g / cm3 , the melt index is 10-20g / 10min.
[0012] Preferably, the outer layer resin and the inner layer resin are PE.
[0013] Preferably, the density of the PE is 0.94-0.96 g / cm 3 , the melt index is 0.2~0.5g / 10min.
[0014] In the present invention, LDPE is selected as the middle layer resin, and PE is selected as the outer layer resin and the inner layer resin. The melting temperature of LDPE is lower than the decomposition temperature of ammonium carbonate, which can ensure that the ammonium carbonate in the silica aerogel will not decompose when the LDPE resin is melted. In addition, LDPE and PE have good compatibility. LDPE as the middle layer resin has high composite strength with the inner layer and the outer layer PE, and no dividing line is generated.
[0015] Preferably, the inner layer blending temperature is 190-200°C.
[0016] Preferably, the outer layer blending temperature is 190-200°C.
[0017] Preferably, the conditions for the three-layer extrusion include: a die outlet temperature of 185-190° C., a screw speed of 35-50 r / min, and a feed speed of 15-30 r / min.
[0018] Preferably, the three-layer extrusion conditions also include: a pulling speed of 250 to 270 r / min.
[0019] Compared with the prior art, this application has the following technical effects: The method immerses the silica aerogel in a saturated ammonium carbonate solution, so that the ammonium carbonate solution is adsorbed into the pores of the silica aerogel, and then the ammonium carbonate is crystallized in the pores of the silica aerogel by drying, and the silica aerogel is filled to significantly increase the weight of the silica aerogel, so that the silica aerogel can be fully mixed in the middle layer resin. In addition, the middle layer blending is divided into a first mixing stage and a second mixing stage. During the first mixing stage, the ammonium carbonate salt will not be decomposed to ensure that the silica aerogel can be evenly mixed in the middle layer resin. The second mixing stage increases the mixing temperature to decompose the ammonium carbonate salt in the silica aerogel into carbon dioxide, ammonia and water for discharge, so as to achieve uniform dispersion of the silica aerogel in the middle layer resin. DETAILED DESCRIPTION
[0020] The present invention will be further described below in conjunction with the embodiments.
[0021] Embodiment 1: A method for preparing a three-layer co-extruded silent composite pipe comprises the following steps: Step 1: immersing silica aerogel (particle size of 100-500 μm) in a saturated ammonium carbonate solution for 10 hours, filtering and collecting the silica aerogel after immersion, and drying the silica aerogel in an oven at 80° C. to prepare a precursor; Step 2: Add the middle layer resin (LDPE, density 0.92g / cm 3 , melt index is 15g / 10min) is placed in a screw mixing device at a temperature of 145°C for melting, the precursor (added amount is 25%) is added to the screw extruder for one-stage blending, the blending time is 2h, the temperature is raised to 195°C for two-stage blending for 2h, and the middle layer melt is prepared after the gas is completely evacuated; Step 3: Apply outer layer resin (PE, density 0.95g / cm 3 , melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an outer layer melt; Step 4: Apply the inner layer resin (PE, density 0.95g / cm 3 , melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an inner layer melt; Step five: The inner layer melt, the middle layer melt and the outer layer melt are respectively placed in three feeding barrels in a three-layer co-extrusion device for three-layer co-extrusion to form a three-layer co-extruded silent composite pipe. The volume ratio of the outer layer melt, the middle layer melt and the inner layer melt is 1.5:7:1.5. The conditions for three-layer co-extrusion are a barrel temperature of 195°C, a die outlet temperature of 190°C, a screw speed of 35r / min, a feeding speed of 20r / min, and a traction speed of 260r / min.
[0022] Embodiment 2: A method for preparing a three-layer co-extruded silent composite pipe comprises the following steps: Step 1: immersing silica aerogel (particle size of 100-500 μm) in a saturated ammonium carbonate solution for 10 hours, filtering and collecting the silica aerogel after immersion, and drying the silica aerogel in an oven at 80° C. to prepare a precursor; Step 2: Add the middle layer resin (LDPE, density 0.91g / cm 3 , melt index is 10g / 10min) is placed in a screw mixing device at a temperature of 140°C for melting, the precursor (added amount is 20%) is added to the screw extruder for one-stage blending, the blending time is 1h, the temperature is raised to 190°C for two-stage blending for 1h, and the middle layer melt is prepared after the gas is completely evacuated; Step 3: Apply outer layer resin (HDPE, density 0.94g / cm 3, melt index is 0.2g / 10min) is placed in a screw extruder and melted at a temperature of 190°C to form an outer layer melt; Step 4: Apply the inner layer resin (HDPE, density 0.94g / cm 3 , melt index is 0.2g / 10min) is placed in a screw extruder and melted at a temperature of 190°C to form an inner layer melt; Step five: The inner layer melt, the middle layer melt and the outer layer melt are respectively placed in three feeding barrels in a three-layer co-extrusion device for three-layer co-extrusion to form a three-layer co-extruded silent composite pipe. The volume ratio of the outer layer melt, the middle layer melt and the inner layer melt is 1.5:7:1.5. The conditions for three-layer co-extrusion are a barrel temperature of 190°C, a die outlet temperature of 185°C, a screw speed of 35r / min, a feeding speed of 15r / min, and a traction speed of 250r / min.
[0023] Embodiment 3: A method for preparing a three-layer co-extruded silent composite pipe comprises the following steps: Step 1: immersing silica aerogel (particle size of 100-500 μm) in a saturated ammonium carbonate solution for 10 hours, filtering and collecting the silica aerogel after immersion, and drying the silica aerogel in an oven at 80° C. to prepare a precursor; Step 2: Add the middle layer resin (LDPE, density 0.93g / cm 3 , melt index is 20g / 10min) is placed in a screw mixing device at a temperature of 150°C for melting, the precursor (addition amount is 30%) is added to the screw extruder for one-stage blending, the blending time is 3h, the temperature is raised to 200°C for two-stage blending for 3h, and the middle layer melt is prepared after the gas is completely evacuated; Step 3: Apply outer layer resin (PE, density 0.96g / cm 3 , melt index is 0.5g / 10min) is placed in a screw extruder and melted at a temperature of 200°C to form an outer layer melt; Step 4: Apply the inner layer resin (PE, density 0.96g / cm 3 , melt index is 0.5g / 10min) is placed in a screw extruder and melted at a temperature of 200°C to form an inner layer melt; Step five: The inner layer melt, the middle layer melt and the outer layer melt are respectively placed in three feeding barrels in a three-layer co-extrusion device for three-layer co-extrusion to form a three-layer co-extruded silent composite pipe. The volume ratio of the outer layer melt, the middle layer melt and the inner layer melt is 1.5:7:1.5. The conditions for three-layer co-extrusion are a barrel temperature of 200°C, a die outlet temperature of 190°C, a screw speed of 50r / min, a feeding speed of 30r / min, and a traction speed of 270r / min.
[0024] Comparative Example 1: Compared with Example 1, Comparative Example 1 does not use sound absorbing material (silicon dioxide aerogel), and includes the following steps: Step 1: Add the middle layer resin (LDPE, density 0.92g / cm 3 , melt index is 15g / 10min) is placed in a screw mixing device and melted at a temperature of 195 to form a middle layer melt; Step 2: Apply outer layer resin (PE, density 0.95g / cm 3 , melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an outer layer melt; Step 3: Apply the inner layer resin (PE, density 0.95g / cm 3 , melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an inner layer melt; Step 4: The inner layer melt, the middle layer melt and the outer layer melt are respectively placed in three feeding barrels in a three-layer co-extrusion device for three-layer co-extrusion to form a three-layer co-extruded silent composite pipe. The volume ratio of the outer layer melt, the middle layer melt and the inner layer melt is 1.5:7:1.5. The conditions for three-layer co-extrusion are a barrel temperature of 195°C, a die outlet temperature of 190°C, a screw speed of 35r / min, a feeding speed of 20r / min, and a traction speed of 260r / min.
[0025] Comparative Example 2: Compared with Example 1, Comparative Example 2 does not use saturated ammonium carbonate solution to treat the silica aerogel, and includes the following steps: Step 1: Add the middle layer resin (LDPE, density 0.92g / cm 3 , melt index is 15g / 10min) is placed in a screw mixing device at a temperature of 145°C for melting, and silica aerogel (particle size is 100-500μm, addition amount is 25%) is added to the screw extruder for one-stage blending, the blending time is 2h, the temperature is raised to 195°C for two-stage blending for 2h, and the middle layer melt is prepared after the gas is completely evacuated; Step 2: Apply outer layer resin (PE, density 0.95g / cm 3 , melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an outer layer melt; Step 3: Apply the inner layer resin (PE, density 0.95g / cm 3 , melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an inner layer melt; Step 4: The inner layer melt, the middle layer melt and the outer layer melt are respectively placed in three feeding barrels in a three-layer co-extrusion device for three-layer co-extrusion to form a three-layer co-extruded silent composite pipe. The volume ratio of the outer layer melt, the middle layer melt and the inner layer melt is 1.5:7:1.5. The conditions for three-layer co-extrusion are a barrel temperature of 195°C, a die outlet temperature of 190°C, a screw speed of 35r / min, a feeding speed of 20r / min, and a traction speed of 260r / min.
[0026] Comparative Example 3: Compared with Example 1, in Comparative Example 3, a saturated ammonium sulfate solution is used to treat the silica aerogel, comprising the following steps: Step 1: immersing silica aerogel (particle size of 100-500 μm) in a saturated ammonium carbonate solution for 10 hours, filtering and collecting the silica aerogel after immersion, and drying the silica aerogel in an oven at 80° C. to prepare a precursor; Step 2: Place the middle layer resin (LDPE, density 0.92g / cm3, melt index 15g / 10min) in a screw mixing device and melt it at a temperature of 145°C, add the precursor (addition amount is 25%) into the screw extruder for one-stage blending, the blending time is 2h, the temperature is raised to 195°C for two-stage blending for 2h, and the middle layer melt is prepared after the gas is completely evacuated; Step 3: Apply outer layer resin (PE, density 0.95g / cm 3 , melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an outer layer melt; Step 4: Apply the inner layer resin (PE, density 0.95g / cm 3 , melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an inner layer melt; Step five: The inner layer melt, the middle layer melt and the outer layer melt are respectively placed in three feeding barrels in a three-layer co-extrusion device for three-layer co-extrusion to form a three-layer co-extruded silent composite pipe. The volume ratio of the outer layer melt, the middle layer melt and the inner layer melt is 1.5:7:1.5. The conditions for three-layer co-extrusion are a barrel temperature of 195°C, a die outlet temperature of 190°C, a screw speed of 35r / min, a feeding speed of 20r / min, and a traction speed of 260r / min.
[0027] Comparative Example 4: Compared with Example 1, in Comparative Example 4, a saturated ammonium chloride solution was used to treat the silica aerogel, comprising the following steps: Step 1: immersing silica aerogel (particle size of 100-500 μm) in a saturated ammonium carbonate solution for 10 hours, filtering and collecting the silica aerogel after immersion, and drying the silica aerogel in an oven at 80° C. to prepare a precursor; Step 2: Add the middle layer resin (LDPE, density 0.92g / cm 3 , melt index is 15g / 10min) is placed in a screw mixing device at a temperature of 145°C for melting, the precursor (added amount is 25%) is added to the screw extruder for one-stage blending, the blending time is 2h, the temperature is raised to 195°C for two-stage blending for 2h, and the middle layer melt is prepared after the gas is completely evacuated; Step 3: Apply outer layer resin (PE, density 0.95g / cm 3 , melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an outer layer melt; Step 4: Apply the inner layer resin (PE, density 0.95g / cm 3 , melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an inner layer melt; Step five: The inner layer melt, the middle layer melt and the outer layer melt are respectively placed in three feeding barrels in a three-layer co-extrusion device for three-layer co-extrusion to form a three-layer co-extruded silent composite pipe. The volume ratio of the outer layer melt, the middle layer melt and the inner layer melt is 1.5:7:1.5. The conditions for three-layer co-extrusion are a barrel temperature of 195°C, a die outlet temperature of 190°C, a screw speed of 35r / min, a feeding speed of 20r / min, and a traction speed of 260r / min.
[0028] Comparative Example 5: Compared with Example 1, the step in Comparative Example 5 is not mixed, and includes the following steps: Step 1: immersing silica aerogel (particle size of 100-500 μm) in a saturated ammonium carbonate solution for 10 hours, filtering and collecting the silica aerogel after immersion, and drying the silica aerogel in an oven at 80° C. to prepare a precursor; Step 2: Add the middle layer resin (LDPE, density 0.92g / cm 3 , melt index is 15g / 10min) is placed in a screw mixing device at a temperature of 145°C for melting, and the precursor (added amount is 25%) is added to a screw extruder for blending to form a middle layer melt, the blending temperature is 195°C, and the blending time is 2h; Step 3: Apply outer layer resin (PE, density 0.95g / cm 3, melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an outer layer melt; Step 4: Apply the inner layer resin (PE, density 0.95g / cm 3 , melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an inner layer melt; Step five: The inner layer melt, the middle layer melt and the outer layer melt are respectively placed in three feeding barrels in a three-layer co-extrusion device for three-layer co-extrusion to form a three-layer co-extruded silent composite pipe. The volume ratio of the outer layer melt, the middle layer melt and the inner layer melt is 1.5:7:1.5. The conditions for three-layer co-extrusion are a barrel temperature of 195°C, a die outlet temperature of 190°C, a screw speed of 35r / min, a feeding speed of 20r / min, and a traction speed of 260r / min.
[0029] Comparative Example 6: Compared with Example 1, in Comparative Example 6, the inner layer resin and the outer layer resin are made of PVA resin, and the following steps are included: Step 1: immersing silica aerogel (particle size of 100-500 μm) in a saturated ammonium carbonate solution for 10 hours, filtering and collecting the silica aerogel after immersion, and drying the silica aerogel in an oven at 80° C. to prepare a precursor; Step 2: Add the middle layer resin (LDPE, density 0.92g / cm 3 , melt index is 15g / 10min) is placed in a screw mixing device at a temperature of 145°C for melting, the precursor (added amount is 25%) is added to the screw extruder for one-stage blending, the blending time is 2h, the temperature is raised to 195°C for two-stage blending for 2h, and the middle layer melt is prepared after the gas is completely evacuated; Step 3: placing the outer layer resin (PVA, S-1000, Qilu Petrochemical) in a screw extruder and melting it at a temperature of 250° C. to form an outer layer melt; Step 4: placing the inner layer resin (PVA, S-1000, Qilu Petrochemical) in a screw extruder and melting it at a temperature of 250° C. to form an inner layer melt; Step five: The inner layer melt, the middle layer melt and the outer layer melt are respectively placed in three feeding barrels in a three-layer co-extrusion device for three-layer co-extrusion to form a three-layer co-extruded silent composite pipe. The volume ratio of the outer layer melt, the middle layer melt and the inner layer melt is 1.5:7:1.5. The conditions for three-layer co-extrusion are a barrel temperature of 250°C, a temperature of 230°C at the die outlet, a screw speed of 35r / min, a feeding speed of 20r / min, and a traction speed of 260r / min.
[0030] Comparative Example 7: Compared with Example 1, the middle layer resin in Comparative Example 7 adopts PVA resin, and comprises the following steps: Step 1: immersing silica aerogel (particle size of 100-500 μm) in a saturated ammonium carbonate solution for 10 hours, filtering and collecting the silica aerogel after immersion, and drying the silica aerogel in an oven at 80° C. to prepare a precursor; Step 2: The middle layer resin (PVA, S-1000, Qilu Petrochemical) was placed in a screw mixing device and melted at a temperature of 250°C, and the precursor (added amount was 25%) was added to the screw extruder for blending to form a middle layer melt. The blending temperature was 250°C and the blending time was 2h; Step 3: Apply outer layer resin (PE, density 0.95g / cm 3 , melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an outer layer melt; Step 4: Apply the inner layer resin (PE, density 0.95g / cm 3 , melt index is 0.35g / 10min) is placed in a screw extruder and melted at a temperature of 195°C to form an inner layer melt; Step five: The inner layer melt, the middle layer melt and the outer layer melt are respectively placed in three feeding barrels in a three-layer co-extrusion device for three-layer co-extrusion to form a three-layer co-extruded silent composite pipe. The volume ratio of the outer layer melt, the middle layer melt and the inner layer melt is 1.5:7:1.5. The conditions for three-layer co-extrusion are a barrel temperature of 195°C, a die outlet temperature of 190°C, a screw speed of 35r / min, a feeding speed of 20r / min, and a traction speed of 260r / min.
[0031] Test example: The pipe properties of the three-layer co-extruded silent PE composite pipes prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were tested; Compatibility: using a 500x magnifying glass to observe whether a dividing line is generated in the cross section; Middle layer status: Use a 500x magnifying glass to observe the cross-section status; Noise test method: Install a 3-meter-long pipe into the drainage system and use a noise meter to test; The test results are shown in Table 1; Table 1 Pipe performance test results Noise(db) Compatibility Middle layer status Example 1 33 No dividing line Sound-absorbing material is evenly dispersed Example 2 38 No dividing line Sound-absorbing material is evenly dispersed Example 3 32 No dividing line Sound-absorbing material is evenly dispersed Comparative Example 1 76 No dividing line / Comparative Example 2 52 No dividing line The sound-absorbing material is unevenly dispersed and has clumps. Comparative Example 3 / No dividing line Yellow patches appear in the middle layer Comparative Example 4 / No dividing line Yellow patches appear in the middle layer Comparative Example 5 / / The sound-absorbing material is unevenly dispersed and has clumps. Comparative Example 6 / There is a dividing line / Comparative Example 7 / There is a dividing line / As shown in Table 1, the noise of the three-layer co-extruded silent composite pipe made in Examples 1 to 3 is 32-38db, there is no dividing line between the three layers, it has a good silent effect, and the compatibility between the layers of the pipe is high and the composite strength is high.
[0032] No sound-absorbing material is used in Comparative Example 1, and the noise is 76db. Compared with Example 1, the noise of Comparative Example 1 is significantly reduced. The above results show that the present invention can significantly improve the quiet effect of the pipe after adding the sound-absorbing material silica aerogel to the middle layer of the pipe.
[0033] In Comparative Example 2, saturated ammonium carbonate was not used to treat the silica aerogel. As a result, the noise of Comparative Example 2 was 52db. After observing the cross-section of the pipe, it was found that the silica was not evenly dispersed in the middle layer, and clusters appeared in the middle layer, resulting in reduced sound absorption effect of the silica aerogel.
[0034] Comparative Examples 3 and 4 respectively selected saturated ammonium chloride solution and saturated ammonium sulfate solution to treat silica aerogel, and it was found that yellow patches appeared in the middle layer of Comparative Examples 3 and 4. After analysis, it is believed that ammonium chloride and ammonium sulfate will produce hydrogen chloride and sulfuric acid when decomposed. These substances are highly oxidizing and will cause the middle layer resin to be oxidized in a high-temperature mixing environment, resulting in the appearance of yellow patches, which will cause the performance of the middle layer resin to change.
[0035] In Comparative Example 5, no mixing was performed. As a result, it was found that the sound-absorbing material in Comparative Example 5 was unevenly dispersed and had agglomerates. After analyzing the results, it was found that when the precursor was directly mixed at high temperature, the temperature exceeded the decomposition temperature of ammonium carbonate, resulting in the decomposition of ammonium carbonate in the silica aerogel. The gas generated during the decomposition caused the silica aerogel to be unable to be effectively mixed with the middle layer resin.
[0036] In Comparative Examples 6 and 7, PVA resin and LDPE were used as the middle layer resin and the inner and outer layer resins. The results showed that there were obvious dividing lines between the inner and outer layers of the three-layer co-extruded pipes. The results show that the three-layer co-extruded pipes made with PE as the inner and outer layer resins and LDPE as the middle layer resin have excellent compatibility.
[0037] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a three-layer co-extruded silent composite pipe, characterized in that: The following steps are involved: The silica aerogel is immersed in a saturated ammonium carbonate solution. After the impregnation, the silica aerogel is dried and crystallized to obtain a precursor. The precursor is mixed with a middle layer resin to obtain a middle layer melt. The inner layer resin is mixed with the inner layer to obtain an inner layer melt. The outer layer resin is mixed with the outer layer to obtain an outer layer melt. The inner layer melt, the middle layer melt and the outer layer melt are extruded to obtain a three-layer co-extruded silent composite pipe. The middle layer mixing includes a first mixing stage and a second mixing stage. The first mixing stage has a mixing temperature of 140-150°C and a mixing time of 1-3 h. The second mixing stage has a mixing temperature of 180-190°C and a mixing time of 1-3 h.
2. The preparation method according to claim 1, characterized in that: The particle size of the silica aerogel is 100-500 μm.
3. The preparation method according to claim 1, characterized in that: The middle layer resin is LDPE.
4. The preparation method according to claim 3, characterized in that: The density of the LDPE is 0.90-0.93 g / cm 3 , the melt index is 10~20 g / 10min.
5. The preparation method according to claim 1, characterized in that: The outer layer resin and the inner layer resin are PE.
6. The preparation method according to claim 5, characterized in that: The density of the PE is 0.94-0.96 g / cm 3 , the melt index is 0.2~0.5 g / 10min.
7. The preparation method according to claim 1, characterized in that: The inner layer blending temperature is 190-200°C.
8. The preparation method according to claim 1, characterized in that: The outer layer blending temperature is 190-200°C.
9. The preparation method according to claim 1, characterized in that: The conditions for the three-layer extrusion include: a die outlet temperature of 185-190° C., a screw speed of 35-50 r / min, and a feed speed of 15-30 r / min.
10. The preparation method according to claim 1 or 9, characterized in that: The three-layer extrusion conditions also include: a pulling speed of 250-270 r / min.
Citation Information
Patent Citations
Silica aerogel sound-absorbing material and sound-generating device
CN109874089B
Three-layer co-extrusion mute drain pipe as well as preparation method and application thereof
CN113085280A
Spiral mute PVC-U pipe
CN217559224U